At the Southeastern end of Schengen accepting refugees in Hungary in 2015's refugees' wave - Nagy Terézia (Belvedere Meridionale, 2018)
In my study I would like to show how the refugees’ situation, motivation and lifestyle have been criminalized in the public discourse (political, press and social public discourse) despite the fact that the Hungarian asylum procedures seem to be converging to the EU standards. I will approach the acceptance of and behaviour towards refugees in two ways: based on my experience from fieldwork carried out in diasporas in Budapest and based on my analysis of the press from the perspective of the host society. These approaches are important because my results show that socio-cultural acceptance is demonstrated almost exclusively by the diasporas even though the economic and official procedures manifest in the body of the host (Hungarian) society. I would also like to speak about the picture the Hungarian media and the government’s discourse show of people crossing the border illegally, how it raises fear and uncertainty among them. This kind of influence conveys messages which hinder fitting in in various aspects, obstruct integration, and at the same time make transnational communication among refugees stereotypical and equivocal. Consequently, ethnically or religiously homogeneous connections are getting stronger, while the importance of diasporas with weak economic, political and advocacy background is also increasing. However, the newcomers hardly ever enter the Hungarian scene.